Freshwater insect communities in urban environments around the globe: a review of the state of the field - Ferzoco, Ilia Maria C.; Murray-Stoker, Kelly M.; Hasan, Lina Salam; Javier, Celina M.; Modi, Vatsaa; Singh, Rupinder; Tjan, Grace; Toth, Olivia; McCauley, Shannon J. (Frontiers in Ecology and Evolution, 2023)
Urbanization is a key stressor of freshwater habitats, possibly contributing to global insect declines. However, scientific understanding of urbanization’s effects on aquatic insect communities has largely been based on studies of temperate streams. We reviewed global urban freshwater macroinvertebrate community studies, classifying habitat type, location, urbanization metrics, biodiversity metrics, and focal taxa, drawing from 114 studies in 32 different countries. Our goals were to: (1) investigate the extent of research on urbanization across a variety of freshwater habitats, (2) examine the representation in empirical literature across the globe by comparing cities in different geographic regions, and (3) highlight how study approaches including taxonomic resolution and the inclusion of trait data impact interpretation of these patterns. Most studies were conducted in North America and Europe, but there is growing representation from other continents. Additionally, lentic environments were underrepresented in the literature on community responses to urbanization compared to lotic studies. Therefore, we suggest that lentic habitats should be investigated more thoroughly. We suggest that future empirical studies should incorporate traits of the taxa investigated to better predict how communities respond to urban stressors. The lack of consistent results from the reviewed studies showed that there is no single, predictable effect of urbanization, indicating that future meta-analyses and review papers should consider the potential context-dependency of freshwater insect responses to anthropogenic pressures. Our goal in highlighting understudied environmental and regional contexts is to move towards holistically addressing the ongoing challenges of urban freshwater insect conservation and freshwater ecology research.